The Influence of Work Ability and Work Motivation on Employee Performance in the Regional Secretariat of Seluma Regency - Gempita Amellia Juniarti; Tito Irwanto; Yesi Indian Ariska (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
The results of the regression equation are Y = 13,962 + 0,257X1 + 0,263X2+3,937, Based on this value, it can be said that work ability and work motivation have a positive influence on employee performance at the Regional Secretariat of Seluma Regency. This illustrates that if the variables of work ability and work motivation increase, the performance of employees will also increase. The result of the determination test area 0.334 or (33.4%). This shows that work ability and work motivation affect employee performance at the Regional Secretariat of Seluma Regency by 33.4%, while the rest (100 - 33.4% = 66.6%) are influenced by other variables not examined. Work ability and motivation to work together have an influence on the performance of the employees of the Regional Secretariat of Seluma Regency which can be seen from the significant value of 0.000 which is smaller than 0.05. It can be seen that there is an increase in work ability and work motivation of employees so that the performance of employees at the Regional Secretariat of Seluma Regency will also increase. Work ability has a positive and significant influence on employee performance at the Regional Secretariat of Seluma Regency, it can be seen from the significant value of 0.000, which is smaller than 0.05. Where the work ability of employees at the Regional Secretariat of Seluma Regency can improve employee performance. Work motivation has a positive and significant effect on employee performance at the Regional Secretariat of Seluma Regency, it can be seen from the significant value of 0.003 which is smaller than 0.05. Where the work motivation of employees at the Regional Secretariat of Seluma Regency can improve employee performance.